Design and Analysis of Broadband Elliptical Microstrip Patch Antenna for Wireless Communication - Ali Khalid Jassim; Raad H. Thaher (Universitas Ahmad Dahlan, 2018)
In this paper presents the design and manufacture of a new broadband elliptical patch antenna with a microstrip feed line and optimum antenna parameters. The antenna dimension of (30×21×1.6) mm3 and fabricated on an FR-4 epoxy substrate having relative dielectric constant ε_r=4.3, loss tangent tan (δ) =0.002 and the feed line used has characteristic impedance of 50Ω.The designed antenna has the capability of operating in the bandwidth (6.95 - 30.94) GHz and the gain (6.8) dBi. The antenna performance was modified by inserting a slots in the ground plane to achieve impedance bandwidth (when S11≤ -10dB) and slots to patch to improve the gain. The modified antenna was designed to be used for fifth generation (5G) mobile communication. The simulation results are obtained using CST software.